A low standby-power fast carbon nanotube ternary SRAM cell with improved stability *Project supported by the National Natural Science Foundation of China (Nos. 61474068, 61234002, 61404076), the S&T Plan of Zhejiang Provincial Science and Technology Department (No. 2016C31078), and the K.C. Wong Magna Fund in Ningbo University, China. (August 2018) - Li, Gang; Wang, Pengjun; Kang, Yaopeng; Zhang, Yuejun
Abstract: Power dissipation, speed and stability are the most important parameters for multiple-valued SRAM design. To reduce the power consumption and further improve the performance of the ternary SRAM cell, we propose a low standby-power fast ternary SRAM cell based on carbon nanotube field effect transistors (CNFETs). The performance is simulated in terms of three criteria including standby-power, delay (write and read) and stability (RSNM). Compared to the novel ternary SRAM cell, our results show that the average standby-power, write and read delay of the proposed cell are reduced by 78.1%, 39.6% and 58.2%, respectively. In addition, the RSNM under process variations is 2.01× and 1.95× of the conventional and novel ternary SRAM cells, respectively.